Meta-Analysis: Inquiry-Based Learning Model in Improving Student Academic Achievement - Fitri Rahmadani, Ade; Syafrijon; Jalinus, Nizwardi; Ridwan; Rijal Abdullah; Nurhasan Syah (AI Society & STMIK Indonesia, 2024)
The purpose of this study is to re-analyze the application of inquiry learning models to improve student academic achievement. Meta-analysis is the type of research in this article. The research stage begins with formulating research problems, the next stage is continued by analyzing research data in accordance with the inquiry learning model. In the process of data collection apply non-test techniques wheresearching for articles contained in electronic journals using the Google Scholar site. 25 scientific articles were obtained from various articles both national and international found based on the inquiry model. In accordance with the results of data analysis, it was obtained that in applying the inquiry learning model in the learning process, there was an increase in student academic achievement. This is evidenced by the lowest value data obtained with a percentage of 3.05% to the highest value with a percentage of 50.99% so that an average of 17.66% is obtained. Then based on the calculation of the effect size of 25 articles used as references, the average effect size value of 7.33% was obtained. From this effect size value, it can be seen that the influence of the inquiry learning model has a very high influence on increasing student academic achievement.